Aromaterapi Citronella Oil Terhadap Peningkatan Nafsu Makan Pada Balita Usia 1-5 Tahun Di Posyandu Tulip Kelurahan Pahandut Palangka Raya - sefentina agustin; Happy Marthalena Simanungkalit; Grisiana Wilianti (Jurnal Skala Kesehatan, 2021)
ABSTRAC Toddlers aged 1-5 years are a group that is prone to nutritional problems. At this time the child is experiencing rapid growth and development, so that it requires adequate and nutritious food intake. Variations in food can increase appetite because of the shape, taste, and attractive color. Attractive shapes in the variety of foods can foster children's curiosity. The purpose of this study was to determine the effect of Citronella Oil aromatherapy on increasing appetite in toddlers aged 1-5 years at the Posyandu Tulip, Pahandut Village, Palangka Raya. This research was carried out for 7 days giving aromatherapy Citronella Oil before going to bed at night. The study design used a Pre Experiment research using One Group Pre-Post Design to 20 respondents with appetite problems. The statistical test used was the Mc Nemar Test. From the Mc Nemar Test results, it was found that p value of appetite = 0,000, then Ha was accepted, meaning that there was an influence of Citronella Oil aromatherapy on increasing appetite in children aged 1-5 years at Posyandu Tulip, Pahandut Palangka Raya Village. Based on the results of this study, researchers suggest that as an alternative therapy to increase appetite and information to parents of toddlers about the influence of aromatherapy citronella oil so as to increase toddlers' appetite. Keywords: Citronella Oil Aromatherapy, Increased appetite, Toddlers aged 1-5 years